2016
DOI: 10.1080/09540121.2016.1179253
|View full text |Cite
|
Sign up to set email alerts
|

Movement between facilities for HIV care among a mobile population in Kenya: transfer, loss to follow-up, and reengagement

Abstract: HIV treatment is life-long, yet many patients travel or migrate for their livelihoods, risking treatment interruption. We examine timely reengagement in care among patients who transferred-out or were lost-to-follow-up (LTFU) from a rural HIV facility. We conducted a cohort study among 369 adult patients on antiretroviral therapy between November 2011 and November 2013 on Mfangano Island, Kenya. Patients who transferred or were LTFU (i.e. missed a scheduled appointment by ≥90 days) were traced to determine if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…Only Wubshet and colleague [39] reported the number of patients who died, survived and returned to HIV care after LTFU. Previous research reported that only 14% and 60% of LTFU patients re-engaged to HIV care at three and six months respectively[64], and those patients who re-engaged accessed the care after their health had deteriorated[65]. This shows a significant oversight for the need of future research involving the role and benefits of establishing the community-tracking system[66].…”
Section: Discussionmentioning
confidence: 99%
“…Only Wubshet and colleague [39] reported the number of patients who died, survived and returned to HIV care after LTFU. Previous research reported that only 14% and 60% of LTFU patients re-engaged to HIV care at three and six months respectively[64], and those patients who re-engaged accessed the care after their health had deteriorated[65]. This shows a significant oversight for the need of future research involving the role and benefits of establishing the community-tracking system[66].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the care outcomes of the patients with an official transfer are unknown. However, data on patients transferring care in the region indicates almost all patients with an official transfer are linked to care at their destination facility within 3 months[38]. Only retention in the first year is captured so longer follow-up will be necessary to evaluate durability of retention in care.…”
Section: Discussionmentioning
confidence: 99%
“…A challenge to ensuring continuity of HIV care is that the fragmented healthcare system is not adapted for a mobile population. Patients considered LTFU actually may have switched facilities on their own as "silent transfers," which typically are not recognized due to unlinked data across facilities [18][19][20]. This misclassification makes it very difficult to accurately assess the effectiveness of national ART programs.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%